Factors associated with prematurity in reported cases of congenital syphilis - Araújo, Maria Alix Leite; Esteves, Ana Beatriz Barbosa; Rocha, Ana Fátima Braga; Junior, Geraldo Bezerra da Silva; Miranda, Angelica Espinosa (Revista de Saúde Pública, 2021)
OBJECTIVE: To analyze the factors associated with prematurity in reported cases of congenital syphilis in the city of Fortaleza, Ceará, Brazil. METHODS: Cross-sectional study conducted in ten public maternity hospitals in Fortaleza, Ceará, Brazil. A total of 478 reported cases of congenital syphilis were included in 2015, and data were collected from notification forms, from mothers’ and babies’ medical records and from prenatal cards. For the bivariate analysis, Pearson’s chi-squared and Fisher’s exact tests were used, considering p < 0.05. Multiple logistic regression was conducted, presenting odds ratio (OR) with a 95% confidence interval. RESULTS: We found 15.3% prematurity in pregnant women with syphilis. The titration of the VDRL test > 1:8 at delivery (OR 2.46; 95%CI: 1.33–4.53; p = 0.004) and the non-treatment of the pregnant women or treatment with drugs other than penicillin during prenatal care (OR 3.52; 95%CI: 1.74–7.13; p< 0.001) were associated with higher chances of prematurity. CONCLUSION: The prematurity due to congenital syphilis is a preventable condition, provided that pregnant women with syphilis are treated appropriately. Weaknesses in prenatal care are associated with this outcome, which highlights the importance of public policies oriented to improve the quality of prenatal care.